2013
DOI: 10.1007/s00296-012-2637-4
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of IL12B polymorphisms (rs3212227, rs6887695) with psoriasis and psoriatic arthritis

Abstract: Interleukin 12 (IL-12) is a key player in model systems of autoimmunity. One of the most robust genetic findings is the association of variants in the IL12B gene with psoriasis and psoriatic arthritis (PsA). This study aims to assess whether combined evidence shows the association between IL12B polymorphisms and the susceptibility to psoriasis/PsA. We conducted a systematic review to examine the association between the IL12B rs3212227 (1188A > C) and rs6887695 and psoriasis/PsA. In addition, we used studies fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
0
22
2
Order By: Relevance
“…IL12 is a proinflammatory cytokine involved in the lymphocyte T helper 1 (Th1) pathway. This cytokine has been widely associated with psoriasis [28][29][30] . Moreover, rs2546890 in IL12 has been associated with psoriasis 26 .…”
Section: Discussionmentioning
confidence: 99%
“…IL12 is a proinflammatory cytokine involved in the lymphocyte T helper 1 (Th1) pathway. This cytokine has been widely associated with psoriasis [28][29][30] . Moreover, rs2546890 in IL12 has been associated with psoriasis 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the involvement of Th17 and underlined the crucial role of IL12 and IL23 in the context of Th17 cell-dependent chronic inflammation [3,11,12,13,14,15]. Psoriasis predisposition polymorphisms in the IL12B gene, encoding for the p40 subunit of IL-12 and IL-23, regulate the amount of p40 produced by cells in response to inflammatory stimuli and the polarization of Th cells in psoriasis [16].…”
Section: Introductionmentioning
confidence: 99%
“…IL-12B is a proinflammatory cytokine that induces T helper 1 (Th1) pathway. Previous publications have suggested that IL-12B plays an important role in psoriasis development [12,44,45]. Furthermore, rs2546890 (IL-12B) is associated with the susceptibility to develop psoriasis [46] and to develop psoriatic arthritis in psoriasis patients [47].…”
Section: Discussionmentioning
confidence: 98%